(3eMGVQGJ aj GbJUGO GdHfhcs - (3TGcQ(B, (3GdbRhjfjs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2008)
(3GdJYQja HGdEFJeGf hHGdefTBJ GdeGdjI hGdfbhO,GdJYQja HGdHfhc,GdfXGe GdeUQaj aj GdLRGFQ,GdhOGFY,GdEFJeGf,YedjGJ eUQajI CNQis
(3GdedGMb(B:(3U U(B.151-158(3;HHdjhZQGajG(B:(3U U(B.159-161s
Keywords: (3GdEbJUGOs; (3GdHfhcs